Distribution Pattern and Sex Ratio of Lokan Shellsfish (Batissa violacea) in the waters of the Padang Birik-birik Village, North Pariaman District, Pariaman City - Adila, Melin; Tanjung, Afrizal; Efriyeldi, Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in January 2019 at the Padang Birik Village, North Pariaman.The purpose of this research was to determine the pattern of distribution, abundance, sex ratio and frequency of lokan shellfish (B. violacea) size. The methods of this research was the survey methods,where the research station consists of 3 stations that werestation 1 in the mangrove area of Padang Birik-birik Village, station 2 was located in the estuary area close to the beach of Padang Birik -birik Village, station 3 was located adjacent to the coastal residential area in the village of Padang Birik –birik.Analysis was carried out in the Marine Biology Laboratory, University of Riau. The results of this study are the distribution pattern in the mangrove ecosystem clustered and the distribution pattern in the residential area were evenly distributed. The highest abundance was found in the mangrove ecosystem and the lowest was in residential areas. Sex ratio are generally male and female are balanced (1: 1.02). The most commonly found class of shellfish size 38,5-49,5 mm.Keywords: Lokan shells (B. Violacea), distribution patterns, abundance, sex ratio, frequency of size